Resurrecting inactive antimicrobial peptides from the lipopolysaccharide trap - Mohanram, Harini (2015)
Host defense antimicrobial peptides (AMPs) are a promising source of antibiotics for the treatment of multiple-drug-resistant pathogens. Lipopolysaccharide (LPS), the major component of the outer leaflet of the outer membrane of Gram-negative bacteria, functions as a permeability barrier against a variety of molecules, including AMPs. Further, LPS or endotoxin is the causative agent of sepsis killing 100,000 people per year in the United States alone. LPS can restrict the activity of AMPs inducing aggregations at the outer membrane, as observed for frog AMPs, temporins, and also in model AMPs. Aggregated AMPs, "trapped" by the outer membrane, are unable to traverse the cell wall, causing their inactivation. In this work, we show that these inactive AMPs can overcome LPS-induced aggregations while conjugated with a short LPS binding β-boomerang peptide motif and become highly bactericidal. The generated hybrid peptides exhibit activity against Gram-negative and Gram-positive bacteria in high-salt conditions and detoxify endotoxin. Structural and biophysical studies establish the mechanism of action of these peptides in LPS outer membrane. Most importantly, this study provides a new concept for the development of a potent broad-spectrum antibiotic with efficient outer membrane disruption as the mode of action.